Key concepts in anti-discriminatory social work - Okitikpi, Toyin; Aymer, Cathy (London ; Thousand Oaks, Calif. : SAGE, 2010)
This Key Concepts clearly and concisely explains the basic ideas in the field of anti-discriminatory social work. It explores the range of discriminations that people experience and discusses a number of theories that inform anti-discriminatory practice ; considers the legal frameworks within which anti-discriminatory practice operates; analyses the skills and knowledge required to practice effectively; highlights the dynamic nature of anti-discriminatory practice and points the way towards a new practice dimension. Provides an essential reference guide for all social work students and practitioners, as well as those taking courses in teacher training, youth and community, nursing, mid-wifery and mental health studies for whom anti-discriminatory practice is an important element in their study.
Pt. 1. Underpinning ideas and concepts. -- 1. The nature of discrimination -- 2. Ideas informing anti-discriminatory practice models -- 3. Models of anti-discriminatory practice -- 4. The political dimension of anti-discriminatory practice -- 5. Legislation and policies -- Pt. 2. Implementation and practice considerations. -- 6. Working with diversity and challenging the status quo -- 7. Key skills, knowledge and anti-discriminatory practice -- 8. Integrating anti-discriminatory practice into social work methods and approaches -- 9. The dynamic nature of anti-discriminatory practice -- 10. Towards a new practice dimension.
Includes bibliographical references (p. 161-166) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social service -- Practice; Discrimination; Social work with minorities; Electronic books